Sex-specific Estrogen Levels and Reference Intervals from Infancy to Late Adulthood Determined by LC-MS/MS - Frederiksen, Hanne; Johannsen, Trine Holm; Andersen, Stine Ehlern; Albrethsen, Jakob; Landersoe, Selma Kløve; Petersen, Jørgen Holm; Andersen, Anders Nyboe; Vestergaard, Esben Thyssen; Schorring, Mia Elbek; Linneberg, Allan; Main, Katharina M; Andersson, Anna-Maria; et al. (The journal of clinical endocrinology and metabolism, 2020)
Abstract Context The lack of sensitive and robust analytical methods has hindered the reliable quantification of estrogen metabolites in subjects with low concentrations. Objective To establish sex-specific reference ranges for estrone (E1) and estradiol (E2) throughout life and to evaluate sex-differences using the state-of-the-art liquid chromatography tandem mass spectrometry (LC-MS/MS) method for quantification of E1, E2, and estriol (E3). Design LC-MS/MS method development and construction of estrogen reference ranges. Settings Population-based cross-sectional cohorts from the greater Copenhagen and Aarhus areas. Participants Healthy participants aged 3 months to 61 years (n = 1838). Results An isotope diluted LC-MS/MS method was developed and validated for measurements of serum E1, E2, and E3. Limits of detections (LODs) were 3 pmol/L (E1), 4 pmol/L (E2), and 12 pmol/L (E3), respectively. This sensitive method made it possible to differentiate between male and female concentration levels of E1 and E2 in children. In girls, E2 levels ranged from <LOD to 100 pmol/L during mini-puberty, whereas it was ≤20 pmol/L during childhood. E1 and E2 increased with age and pubertal breast stage and varied during the menstrual cycle; E1 was lower than E2 in girls and premenopausal women, and higher than E2 in postmenopausal women. In boys, E1 and E2 increased with age and pubertal stage, whereas little changes with age were observed in men. High E3 concentrations were confirmed in pregnant women. Conclusion Reference ranges of simultaneous quantification of E1 and E2 by this novel specific and highly sensitive LC-MS/MS method provide an invaluable tool in clinical practice and in future research studies.